The Development of the Teacher as a Professional in an Alternative Teacher Education Program - Pascarelli, Joseph T.; Ackley, Blaine C.; Balaban, Gerald M. (Catholic Education: A Journal of Inquiry and Practice, 2001)
Recruitment and retention strategies are a growing concern for Catholic educational leaders. This article offers a glimpse into the dynamics of a leading teacher recruitment effort, the Alliance for Catholic Education (ACE) sponsored by the University of Notre Dame. After surveying the first two cohorts who taught in Catholic schools through ACE, the authors uncover significant and meaningful components of this alternative teacher preparation program with a view to challenging traditional teacher education efforts and preservice requirements.